2023
DOI: 10.1111/ahe.12900
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and pathological characteristics of ribs in the Atlantic salmon (Salmo salar L.) and its relevance to soft tissue changes

Abstract: Studies on the anatomical and pathological characteristics of ribs in farmed Atlantic salmon (Salmo salar L.) are warranted due to their possible association with red and melanized focal changes (RFC and MFC) in the fillet, a major quality and animal welfare concern. In this work, we provide an anatomical description of ribs based on radiographical and histological analyses. We also address various pathological rib changes and their association to RFC and MFC. In total, 129 fish were investigated; captured wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…1 ). Despite numerous suggested causes (Bjorgen et al 2020 ; Brimsholm et al 2023 ; Jimenez-Guerrero et al 2023 ), the underlying etiology of RFC and its subsequent progression to MFC remains elusive.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Despite numerous suggested causes (Bjorgen et al 2020 ; Brimsholm et al 2023 ; Jimenez-Guerrero et al 2023 ), the underlying etiology of RFC and its subsequent progression to MFC remains elusive.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, may lead to a chronic, granulomatous inflammation with organized granulomas, as the immune system attempts to ‘wall off’ the infection (Bjørgen et al, 2015). Various theories have been proposed to explain the cause of RFC/MFC, including external trauma, vaccination and costal fractures (Brimsholm et al, 2023; Jiménez‐Guerrero et al, 2022; Koppang et al, 2005). Impaired oxygen transport resulting from abnormal heart morphology and function in farmed salmon (Johansen et al, 2017; Poppe et al, 2003) has also been suggested as a potential cause for ischemia and necrosis of myocytes.…”
Section: Introductionmentioning
confidence: 99%